Computerized logistics information systems - a key to competitiveness - Čižman, Anton (Informatica (Ljubljana), 2001)
Part of an organization's ability to use logistics as a competitive weapon is based on its ability to assess and adjust actual logistics performance real time. This means the ability to monitor customer demands and inventory levels as they occur, to act in timely manner to prevent stockouts, and communicate potential problems to customers. This requires excellent, integrated logistics systems which impact all of the logistics activities. In this paper we examined how computer and information technology can be used to support logistics management. Customer order cycle and order processing systems are pointed out first. Then advanced information technologies such as decision support systems, artificial intelligence, and expert systems which are being used directly to suppot decision making in logistics, are examined.
Keywords: informacijski sistemi; management; sistemi za pomoč pri odločanju; informacijska tehnologija; information technology; proizvodnja; storitve